ALTERNATIVES TO STATINS IN THE TREATMENT OF HYPERCHOLESTEROLEMIA - Agnieszka Bajkacz (International Journal of Innovative Technologies in Social Science, 2026)
Hypercholesterolemia is one of the main modifiable risk factors for cardiovascular disease. Elevated levels of LDL (low-density lipoprotein) cholesterol lead to the development of atherosclerosis and cardiovascular complications. Statins are the mainstay of hypercholesterolemia therapy, but in some patients, therapeutic goals are not achieved or side effects occur. It is necessary to develop alternatives to statins for the treatment of hypercholesterolemia. Drugs that act on other stages of cholesterol synthesis are being sought. Publications covering observational studies, randomized controlled trials (RCTs), and meta-analyses on alternative therapies for hypercholesterolemia to statin treatment were analyzed. The following were described: cholesterol absorption inhibitor (ezetimibe), ATP citrate lyase inhibitor (bempedoic acid), PCSK9 inhibitors (evolocumab, alirocumab) , siRNA against PCSK9 (inclisiran), ANGPTL3 inhibitors (evinacumab), ANGPTL4, ANGPTL8 and ANGPTL3/8 complex inhibitors, fibrates and nutraceuticals (plant sterols, fermented red yeast rice extract (Red Yeast Rice, RYR) , berberine). The impact of these drugs on patients’ lipid profiles and cardiovascular risk was discussed. Attention was also drawn to the need for individualization of hypercholesterolemia therapy. Aim of this study: The objective of this study is to summarize the latest reports on alternative therapies for hypercholesterolemia to statins. Materials and methods: A literature review was conducted using the professional PubMed database. Searches included combinations of the keywords: “hypercholesterolemia,” “ezetimibe,” “bempedoic acid,” and “PCSK9 inhibitors.”